1999
DOI: 10.1144/sjg35020119
|View full text |Cite
|
Sign up to set email alerts
|

Middle Hettangian (Lower Jurassic) ammonites from Isle of Raasay, Inner Hebrides, and correlation of the Hettangian-lowermost Sinemurian Breakish Formation in the Skye area, NW Scotland

Abstract: SynopsisLiasicus Zone (middle Hettangian) ammonites, allocated to a new species, Franziceras sorleyi, are described from Hallaig, Isle of Raasay and indicate that the Breakish Formation / ^v (formerly lower Broadford Beds) there is older than previously thought. The new finds have / ^jIjT \ been integrated with the limited available biostratigraphic information from the rare records I tfT^ /fT% 1 of Hettangian and basal Sinemurian ammonites, and with local lithostratigraphy based I «^S K "H I on marker beds, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In the case of the Hebrides Basin, NW Scotland, Amiri-Garoussi (1977) suggested that locally derived smectite-rich assemblages of the Hettangian-earliest Sinemurian Lower Broadford beds (now Breakish Formation;Morton 1999) were replaced upwards by a mixture of illite and kaolinite in the Sinemurian, because the smectite sources had been either depleted or buried beneath onlapping sediment. As in the Hebridean area, so in southern England the Hettangian and Sinemurian interval is characterized by onlap on Hercynian massifs such as the London Platform (Donovan et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the Hebrides Basin, NW Scotland, Amiri-Garoussi (1977) suggested that locally derived smectite-rich assemblages of the Hettangian-earliest Sinemurian Lower Broadford beds (now Breakish Formation;Morton 1999) were replaced upwards by a mixture of illite and kaolinite in the Sinemurian, because the smectite sources had been either depleted or buried beneath onlapping sediment. As in the Hebridean area, so in southern England the Hettangian and Sinemurian interval is characterized by onlap on Hercynian massifs such as the London Platform (Donovan et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The 14 plant‐bearing horizons identified within the Bearreraig Sandstone Formation span deposits extending from the middle of the Opalinum Zone of the Dun Caan Shale Member to the top of the Laeviuscula Zone in the Holm Sandstone Member (Fig. 1C; Morton and Hodson, 1995). The Bearreraig Sandstone Formation represents a succession of shallow marine sediments, into which fossil plants rafted from surrounding land areas (Bateman and Morton, 1994; Bateman et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…The contact is obscured by approximately 10 m of dead ground at Neist Point, but the first exposed eruptive deposits comprise subaerial sheet lavas. The sedimentary rocks below the subaerial lavas are dominated by Middle Jurassic shallow marine siliciclastic sediments (Searl, 1994;Morton, 1999;Hesselbo and Coe, 2000) and estuarine strata with many coarse-grained facies, crossbedding sedimentary structures, and nonmarine shales (Morton, 1983;Harris, 1989). The subbasalt sediments have locally been extensively intruded by dolerite sheet intrusions.…”
Section: Onshore: Isle Of Skye Scotlandmentioning
confidence: 99%